wireless Robot controlled by hand gesture - Al-Haj, Waed (My University, 2019)
In today’s era human-machine interaction is becoming widespread. So, with the introduction of new technologies the gap between machines and humans is being reduced to ease the standard of living. Gestures have played a crucial role in diminishing this gap. This paper deals with design and implementation of an accelerometer-based hand gesture-controlled robot controlled wirelessly using a small low cost, 3-axis accelerometer. The project can be used in surveillance, especially in education and entertainment. The robot which can be controlled by simple human gestures. The user just needs to wear a gesture device in which a sensor is included. The sensor will record the movement of hand in a specific direction which will result in the motion of the robot in the respective directions. The robot and the Gesture movement are connected wirelessly through Bluetooth. User can interact with the robot in a more friendly way due to the wireless communication. We can control the car using accelerometer sensors connected to a hand glove. The sensors are intended to replace the remote control that is generally used to run the car. It will allow user to control the forward, backward, leftward and rightward movements.
“surveillance and education toy robot”